POTENTIAL OF ENDOPHYTIC FUNGI DERIVING FROM ASIATIC PENNYWORTH TO PRODUCE ANTIOXIDANTS - Dwi Ningsih Susilowati; Nani Radiastuti; Nurhasni Nurhasni; Lisca Puji Rustanti; Ika Roostika Tambunan (Indonesian Journal of Agricultural Science, 2021)
Asiatic pennyworth is a medicinal plant that contains triterpenoids, saponin, flavonoids, and tannins which possess antioxidants. Endophytic fungi from the plant could produce a similar compound; therefore, antioxidants could be made in the laboratory if the fungi are isolated. This study aimed to evaluate the potential of endophytic fungi isolated from Asiatic pennyworth to produce antioxidants. The study used 34 endophytic fungal isolates from Asiatic pennyworth accessions of Malaysia (17 isolates) and Bengkulu, Indonesia (17 isolates) collected by the Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development. The fungi were propagated in a potato dextrose broth medium, then mycelia mats and filtrates were separated and then freeze-dried. The antioxidant activities were first tested with 1,1-diphenyl-2- picrylhydrazyl (DPPH) using thin layer chromatography (TLC), then UV-Vis spectrophotometry λ517 nm with five variations of concentration. Results showed all 34 fungal isolates have antioxidant activities based on a yellowish-white color change after applying 0.002% DPPH solution of the TLC method and IC50 value of the UV-Vis spectrophotometer. The highest antioxidant activity was shown by Aspergillus austroafricanus MB 1 (IC50 = 12.08 ppm) from Bengkulu accession and A. oryzae MM 13 (IC50 = 10.29 ppm) from Malaysia accession. A. austroafricanus MB 1 produced more antioxidant compounds (seven) than A. oryzae MM 13 (six). The antioxidant compounds produced by both endophytic fungi included in the group of flavonoids, fatty acids, and carboxylic acids. The research implies that A. austroafricanus MB 1 and A. oryzae MM 13 could be further developed as sources of antioxidants.